To study the implication of occupational stress toward employee job performance at Noor Arfa Holdings Sdn. Bhd. / Nurul 'Athifah Alias - Alias, Nurul 'Athifah (Faculty of Business and Management, 2018)
The purpose of the study is to investigate the relationship between occupational stress toward employee job performances. Factors that has been included in the study are workload, poor working conditions, role ambiguity also inadequate monetary rewards. There were two objectives for this research which are to identify the level of the employee's job performances also to examine the relationship between occupational stress and employee job performance Method that has been used to conducting the research are correlational and the selected respondent has been choose by using simple random table for the sampling technique at Noor Arfa Holdings Sdn. Bhd. Out of 70 set of questionnaires that had been dispersed, only 65 set of questionnaires able to be collected back and another 5 set of questionnaires were missing. Based on the research that has been conduct, I can conclude that although, there were high turnover rates from the employees at Noor Arfa Holdings Sdn. Bhd. The finding result shows all the variables of occupational stress have significant relationship towards employee job performances. But, all the employee at this company can perform their work under stress but they need the reward to be increase in the company as the employees seem agree to improve their performances if there were monetary or any rewards offered to them